Difficulties in the diagnosis of light spots. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
The differential diagnosis between nevus anemicus (NA) and nevus depigmentosus (ND) is facilitated by some maneuvers such as pressure of the fingers which makes only NA disappear and the rubbing: with the latter maneuver ND reddens like the peripheral skin, whereas NA does not redden differently from the peripheral skin (2). Even the differential diagnosis between nevus depigmentosus and vitiligo is usually easy: ND is more precocious, does not redden and does not repigment with the sun, and remains unchanged over time. Vitiligo reddens and can partially repigment with the sun, and changes over time (1). In this case the diagnosis was less easy due to the imprecision of the clinical history and the poor visibility of the two lesions. Wood light was diriment leaving unchanged nevus depigmentosus, while it significantly accentuated vitiligo, also highlighting two areas of repigmentation.